Membrane electrode solid electrolyte for synthesizing pure liquid product through electrochemical reduction of CO2 and application
By modifying the solid electrolyte of MOF base film electrode, the problems of gas diffusion and reaction system in the existing electrochemical reduction CO2 technology are solved, and efficient and stable CO2 reduction reaction is achieved, and the selectivity and purity of the product are improved.
Patent Information
- Application Number
- CN202411782718.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-06
AI Technical Summary
The existing electrochemical reduction CO2 technology has problems such as gas diffusion, unstable reaction system, and poor product selectivity. Especially after a long period of operation, the cations in the electrolyte will bind to the carbonate on the catalyst surface, resulting in a decrease in CO2 reduction reaction performance.
Using a modified MOF base film electrode solid electrolyte, a MOF crystal is formed by reacting zinc nitrate and 2-methylimidazole in methanol, and mixed it uniformly with the polymer matrix to form a modified MOF base film electrode solid electrolyte. The electrolyte has a high surface area and a rich pore structure, which can improve ion transport efficiency, enhance mechanical strength, and selective adsorption and transport of specific ions or molecules through the selective adsorption and transport of specific ions or molecules, thereby improving the efficiency and product purity of CO2 reduction reaction.
It realizes efficient and stable CO2 reduction reaction, improves current density and product selectivity, ensures stability for long-term operation, and improves product purity and Faraday efficiency.
Smart Images

Figure CN119615223A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new energy materials, and in particular to a membrane electrode solid electrolyte (modified MOF-based membrane electrode solid electrolyte) for electrochemically reducing CO2 to synthesize pure liquid products. Background Art
[0002] With the acceleration of global industrialization, the extensive use of fossil fuels has led to a sharp increase in carbon dioxide (CO2) emissions, triggering serious greenhouse effect and climate change problems. Converting CO2 into valuable chemicals or fuels not only helps reduce greenhouse gas emissions, but also provides a sustainable carbon source for the chemical industry. Electrochemical reduction of CO2 technology has become a frontier field of research and application due to its advantages such as operation at room temperature and pressure, strong adjustability and high product selectivity.
[0003] Electrochemical reduction of CO2 (CO2RR) is a process that converts CO2 into a variety of products (such as formic acid, carbon monoxide, methanol, ethylene, etc.) through electrochemical methods, involving complex reaction mechanisms and multi-step electron transfer reactions. Traditional electrochemical reduction of CO2 technology mainly uses liquid electrolytes to carry out gas-liquid interface reactions in H-type electrolytic cells. The CO2 reduction rate is limited by its dissolution rate in the electrolyte, and the current density is generally lower than -100mAcm -2 To solve the gas diffusion problem, the flow electrolysis cell uses a hydrophobic gas diffusion layer as the working electrode, and performs CO2 reduction reaction at the solid-liquid-gas three-phase liquid surface. The current density can be increased to -200mAcm -2 However, the three-phase interface is easily destroyed and the reaction system is difficult to maintain stability.
[0004] In order to overcome the above problems, research on solid electrolytes and membrane electrode reactors has gradually emerged. Solid electrolytes have high ionic conductivity, good mechanical properties and excellent electrochemical stability, which can effectively solve the leakage and corrosion problems of liquid electrolytes. The membrane electrode reactor combines the catalyst layer and the ion conductor to achieve efficient interfacial mass transfer and charge transfer, which helps to improve the rate and selectivity of the CO2 reduction reaction. Li et al. (Nature, 2020, 577(7791): 509-513) conducted a stability test of CO2 reduction in a membrane electrode electrolyzer. At a total current of -600mA, FE C2H4 The rate of CO2 reduction reached 64% and it ran stably for 190 hours. Although the membrane electrode electrolysis cell has better stability than the flow electrolysis cell, after running for a long time in the alkaline anode liquid, the cations in the electrolyte will cross the anion exchange membrane, combine with the carbonate ions on the catalyst surface to form salts and precipitate at the cathode, which will reduce the performance of the CO2 reduction reaction. In addition, the products obtained by the CO2 reduction reaction have different phases, and the selectivity of a single product is a great challenge.
[0005] In summary, there are still some challenges in the application of current electrolytes in electrochemical CO2RR. The existing technology mainly uses liquid electrolytes, and the products obtained by the reaction are multiphase and have poor selectivity. In this context, it is particularly important to develop an efficient and stable MOF (Metal-Organic Frameworks) modified polymer solid electrolyte system for electrochemical reduction of CO2 to synthesize pure liquid products. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide an efficient and stable membrane electrode solid electrolyte system and its use. The present invention realizes an efficient and stable CO2 reduction reaction by optimizing the material selection of the membrane electrode solid electrolyte system.
[0007] In order to solve the above technical problems, the present invention provides a method for preparing a modified MOF-based membrane electrode solid electrolyte (a MOF-based membrane electrode solid electrolyte for electrochemical reduction of CO2 to synthesize pure liquid products), comprising the following steps:
[0008] 1) Dissolve zinc nitrate (zinc nitrate hexahydrate) in methanol to obtain a zinc nitrate solution with a concentration of 0.02M to 0.06M; dissolve 2-methylimidazole in methanol to obtain a 2-methylimidazole solution with a concentration of 0.04M to 0.12M; the molar ratio of zinc nitrate to 2-methylimidazole is 1:2;
[0009] Add 2-methylimidazole solution to zinc nitrate solution (addition time is about 8 to 12 minutes), stir and mix (stirring time is 20 to 40 minutes), and then stand at room temperature for 12 to 24 hours to form MOF crystals;
[0010] The MOF crystals were washed with ethanol (to remove the residual reactants, zinc nitrate and 2-methylimidazole, and the solvent methanol); the washed MOF crystals were vacuum dried (in a vacuum drying oven at 60±10° C. for 12±1 h) to obtain MOF powder;
[0011] Note: MOF crystals can be separated by centrifugation or filtration;
[0012] 2) Add tetrafluoroethylene and perfluorovinyl ether into the reactor, then add comonomer and free radical initiator to start the polymerization reaction. The polymerization temperature is 70±10℃ and the reaction time is 8±0.5h;
[0013] The polymer prepolymer obtained by the polymerization reaction is subjected to heat treatment (to enhance the interaction and stability between its chain segments) to obtain a polymer; and then the obtained polymer is dissolved in a solvent to obtain a polymer slurry (for subsequent physical mixing and film forming processes), wherein the concentration of the polymer in the polymer slurry is 10-20wt%;
[0014] Tetrafluoroethylene:perfluoroethylene ether = 1:1 molar ratio,
[0015] Tetrafluoroethylene: comonomer = 1:0.1 molar ratio;
[0016] Tetrafluoroethylene: free radical initiator = 1:0.05 molar ratio;
[0017] 3) adding the MOF powder obtained in step 1) to the polymer slurry (polymer matrix) obtained in step 2) and mixing them evenly to obtain a MOF-modified mixture;
[0018] MOF powder: polymer = 10-20wt%;
[0019] 4) Coating the MOF-modified mixture on a pre-cleaned substrate to form a thin film; then drying (to remove the solvent), and then drying at 80±10°C for 12±1h to solidify the film (i.e., to completely solidify and form a solid solid electrolyte film), and finally separating the film from the substrate to obtain a modified MOF-based membrane electrode solid electrolyte.
[0020] Note: Drying can be done by placing the sample in a fume hood to allow the solvent (N-methyl-2-pyrrolidone and any solvent that may remain during pretreatment of the substrate) to evaporate slowly until constant weight is achieved, which takes about 1 hour.
[0021] As an improvement of the preparation method of the modified MOF-based membrane electrode solid electrolyte of the present invention, in the step 2):
[0022] The comonomer is fluorosulfonic acid, and the free radical initiator is ammonium persulfate;
[0023] Heat treatment is heating at 150±10℃ for 2±0.1h;
[0024] The solvent was NMP (N-methyl-2-pyrrolidone).
[0025] As a further improvement of the method for preparing the modified MOF-based membrane electrode solid electrolyte of the present invention, the uniform mixing in step 3) is stirring or ultrasonic treatment (stirring time is about 1±0.2 hours, ultrasonic treatment time is 30±5 minutes).
[0026] As a further improvement of the method for preparing the modified MOF-based membrane electrode solid electrolyte of the present invention, in the step 4), the coating is performed by spin coating, the rotation speed of the spin coater is set to 1800-2200 rpm, and the coating time is 25-35 seconds.
[0027] As a further improvement of the preparation method of the modified MOF-based membrane electrode solid electrolyte of the present invention, in the step 4): the substrate is a glass substrate or a silicon substrate, and acetone, isopropanol, and deionized water are used to rinse the substrate in sequence to obtain a pre-cleaned substrate.
[0028] As a further improvement of the method for preparing the modified MOF-based membrane electrode solid electrolyte of the present invention, in step 1), the concentration of the zinc nitrate solution is 0.02M to 0.04M, and the concentration of the 2-methylimidazole solution is 0.04M to 0.08M.
[0029] The present invention also provides the use of the modified MOF-based membrane electrode solid electrolyte prepared by the above method: for CO2 reduction, that is, for electrochemical reduction of CO2 to synthesize pure liquid products.
[0030] As an improvement of the use of the present invention: the modified MOF-based membrane electrode solid electrolyte is sandwiched between the cathode (Ag) and the anode (Pt) to ensure that the modified MOF-based membrane electrode solid electrolyte is in close contact with the electrodes; CO2 is electrochemically reduced to formate ions at the cathode.
[0031] The steps for CO2 reduction using the above electrolyte are as follows:
[0032] 1) Sandwich the electrolyte film between the cathode (Ag) and the anode (Pt), ensuring that the membrane is in close contact with the electrodes. Connect the CO2 gas inlet system to the gas diffusion electrode (GDE) on the cathode side and adjust the CO2 flow rate to 20 sccm using a gas flow controller.
[0033] 2) Place the electrolytic cell in a constant temperature water bath or thermostat, and set the temperature to 25±2°C. Connect the cathode and anode to the electrochemical workstation, set the potential scan range to -1.0V to 0V (relative to the standard hydrogen electrode, SHE), and the scan rate to 10mV / s. Start to introduce CO2 gas, so that it enters the cathode chamber through the GDE, and maintain a steady flow rate. Apply a constant potential for the electrolysis reaction, and the reaction time is 2±0.2h.
[0034] 3) After the reaction is completed, collect the liquid sample in the cathode chamber and analyze it using a mass spectrometer or a gas chromatograph.
[0035] The technical advantages of the present invention are:
[0036] 1) MOF-based materials have high surface area and rich pore structure, which can improve ion transfer efficiency, reduce membrane resistance, and thus improve electrochemical reaction efficiency.
[0037] 2) MOF and polymer matrix (polymer slurry) are resistant to chemical corrosion and degradation, enhancing the mechanical strength of the membrane and ensuring long-term stable use.
[0038] 3) The pores and functional groups of MOF selectively adsorb and transport specific ions or molecules, improving the efficiency of the CO2 reduction reaction and the purity of the product. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] The specific implementation modes of the present invention are further described in detail below with reference to the accompanying drawings.
[0040] Figure 1 Schematic diagram of a membrane electrode electrolyzer for electrochemical reduction of CO2;
[0041] In the figure: 1. cathode flow channel plate; 2. cathode GDE; 3. solid electrolyte; 4. anode GDE; 5. anode flow channel plate. DETAILED DESCRIPTION
[0042] The following is a detailed description of an embodiment of the present invention. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and a specific operation process.
[0043] In the present invention:
[0044] Zinc nitrate hexahydrate, ie, zinc nitrate hexahydrate.
[0045] Fluorosulfuric acid, ie, fluorosulfonic acid.
[0046] Example 1. Preparation of solid electrolyte film
[0047] 1) Weigh zinc nitrate hexahydrate (0.002 mol) and dissolve it in 100 mL of methanol to obtain a zinc nitrate solution with a concentration of 0.02 M;
[0048] Weigh 2-methylimidazole (0.004 mol) and dissolve it in 100 mL of methanol to obtain a 0.04 M 2-methylimidazole solution;
[0049] Under stirring, slowly add 2-methylimidazole solution to zinc nitrate solution (addition time is about 10 minutes), and then mechanically stir and mix for 30 minutes after the addition is completed, and then let the mixture stand at room temperature for 12 hours to promote the formation of MOF crystals;
[0050] After the above-mentioned standing, the mixture was filtered and the obtained filter residue (MOF crystals) was washed with ethanol to remove the residual reactants (including zinc nitrate and 2-methylimidazole) and the solvent (methanol); the washed MOF crystals were dried in a vacuum drying oven at 60° C. for 12 h to obtain MOF powder (pure MOF powder).
[0051] 2) Add 0.1 mol of tetrafluoroethylene and 0.1 mol of perfluorovinyl ether into a reactor, add 0.01 mol of fluorosulfonic acid as a comonomer, use 0.005 mol of a free radical initiator (such as ammonium persulfate) to start the polymerization reaction, control the reaction temperature at 70°C, and react for 8 hours to form a polymer prepolymer.
[0052] The polymer prepolymer is heat treated at 150° C. for 2 hours to enhance the interaction and stability between the chain segments to obtain a polymer;
[0053] The obtained polymer was dissolved in NMP (N-methyl-2-pyrrolidone) to prepare a polymer slurry with a concentration of 10 wt % for subsequent physical mixing and film forming processes.
[0054] 3) gradually adding the MOF powder obtained in step 1) to the polymer slurry obtained in step 2) (addition time is about 5 minutes); the amount of MOF powder added is 10wt% of the polymer mass, and then stirring for 1 hour or ultrasonic treatment for 30 minutes, so that the MOF is uniformly dispersed in the polymer matrix (polymer slurry) to form a MOF modified mixture.
[0055] 4) Using acetone, isopropanol, and deionized water to rinse the glass substrate or silicon substrate in sequence to obtain a pre-cleaned glass substrate or silicon substrate;
[0056] The MOF-modified mixture obtained in step 3) is evenly coated on a pre-cleaned glass substrate or silicon substrate by spin coating. The speed of the spin coater is set to 2000 rpm, and the coating time is 30 seconds. The coated substrate is placed in a fume hood to allow the solvent (N-methyl-2-pyrrolidone and the solvent that may be left when pretreating the substrate) to evaporate slowly, which takes about 1 hour (until the mass of the substrate and the coating material no longer decreases). The coated substrate is placed in an oven at 80°C and dried for 12 hours to completely solidify and form a solid electrolyte film; finally, the film is separated from the substrate to obtain a membrane electrode solid electrolyte (thickness is about 100 μm).
[0057] Experiment 1: CO2 reduction using electrolytes
[0058] Figure 1It is a schematic structural diagram of a membrane electrode electrolyzer device for electrochemical reduction of CO2 of the present invention, which can refer to "A Visualized Cathode Channel Plate Structure and Electrolyzer Structure" of 202311778869.4, including a cathode channel plate 1, a cathode GDE (cathode gas diffusion layer) 2, a solid electrolyte 3, an anode GDE (anode gas diffusion layer) 4, and an anode channel plate 5;
[0059] A cathode flow channel is provided in the cathode flow channel plate 1, an anode flow channel is provided in the anode flow channel plate 5, a membrane electrode solid electrolyte 3 is provided between the cathode GDE2 and the anode GDE4, a cathode flow channel plate 1 is provided on the outer side of the cathode GDE2, and an anode flow channel plate 5 is provided on the outer side of the anode GDE4.
[0060] The cathode (Ag) includes a cathode flow channel plate 1 and a cathode GDE2, and its catalytic active material is Ag; the anode (Pt) includes an anode flow channel plate 1 and an anode GDE2, and its catalytic active material is Pt. The electrolyte film (i.e., the membrane electrode solid electrolyte 3) is sandwiched between the cathode (Ag) and the anode (Pt) to ensure that the membrane is in close contact with the electrode.
[0061] The working process is as follows:
[0062] 1) The CO2 gas injection system passes through the cathode flow channel plate 1 to the gas diffusion electrode (cathode GDE2) on the cathode side, and uses a gas flow controller to adjust the CO2 flow rate to 20 sccm.
[0063] 2) Place the entire membrane electrode electrolysis cell device in a constant temperature water bath or thermostat, and set the temperature to 25°C. Connect the cathode GDE2 and the anode GDE4 to the electrochemical workstation, set the potential scan range to -1.0V to 0V, and the scan rate to 10mV / s. Start the flow of CO2 gas, allow the CO2 gas to enter the cathode chamber, and maintain a stable flow rate. Apply a constant potential for the electrolysis reaction. During the electrolysis process, CO2 is continuously introduced to maintain a stable concentration, and CO2 is electrochemically reduced to formate ions at the cathode.
[0064] 3) After the reaction time (2 hours) is over, stop the inflow of CO2 and collect the product sample at the cathode, and use a mass spectrometer or gas chromatograph for quantitative analysis. The Faraday efficiency of the liquid product is 98%. The product purity is 99%.
[0065] Faraday efficiency calculation formula:
[0066] In the above formula, n is the number of moles of the target product formic acid (HCOOH) generated, which can be obtained by quantitative analysis by mass spectrometer or gas chromatograph. F is the Faraday constant, which is about 96485C / mol. z is the number of electrons required to generate the target product in the electrochemical reaction. Q is the total charge, which is equal to the current I multiplied by the time t, that is, Q = I × t.
[0067] The product purity calculation formula is: Purity = mass of target product (HCOOH) / total mass of all collected products × 100%.
[0068] Embodiment 2: With respect to Embodiment 1, the following changes are made:
[0069] Weigh zinc nitrate hexahydrate (0.004 mol) and dissolve it in 100 mL of methanol to obtain a zinc nitrate solution with a concentration of 0.04 M;
[0070] Weigh 2-methylimidazole (0.008 mol) and dissolve it in 100 mL of methanol to obtain a concentration of 0.08 M in 100 mL of methanol.
[0071] The rest is the same as Example 1.
[0072] The obtained electrolyte film was used for CO2 reduction according to Experiment 1, and the Faraday efficiency of the liquid product was 97.6% and the product purity was 98%.
[0073] Embodiment 3, compared with embodiment 1, makes the following changes:
[0074] The standing time in step 1) was changed from 12 h to 24 h, and the rest was the same as in Example 1.
[0075] The obtained electrolyte film was used for CO2 reduction according to Experiment 1, and the Faraday efficiency of the liquid product was 96.8% and the product purity was 97%.
[0076] Embodiment 4: With respect to Embodiment 1, the following changes are made:
[0077] The step 2) of "preparing a polymer slurry with a concentration of 10 wt %" is changed to "preparing a polymer slurry with a concentration of 20 wt %"; the rest is the same as Example 1.
[0078] The obtained electrolyte film was used for CO2 reduction according to Experiment 1, and the Faraday efficiency of the liquid product was 97.2% and the product purity was 97%.
[0079] Embodiment 5, with respect to embodiment 1, the following changes are made:
[0080] In step 3), "the amount of MOF powder added is 10 wt% of the mass of the polymer" is changed to "the amount of MOF powder added is 20 wt% of the mass of the polymer", and the rest is the same as in Example 1.
[0081] The obtained electrolyte film was used for CO2 reduction according to Experiment 1, and the Faraday efficiency of the liquid product was 95.9%, and the product purity was 95%.
[0082] Comparative Example 1: The following changes were made relative to Example 1:
[0083] Cancel step 2);
[0084] Step 3) is changed to: the MOF powder obtained in step 1) is gradually added into NMP, and the amount of NMP used is the same as that in Example 1; and then stirred for 1 hour to form a 10 wt% MOF solution.
[0085] In step 4), the above MOF solution is used for spin coating, and the rest is the same as in Example 1.
[0086] The obtained electrolyte film was used for CO2 reduction according to Experiment 1, and the Faraday efficiency of the liquid product was 64.2% and the product purity was 64%.
[0087] Comparative Example 2: The following changes were made relative to Example 1:
[0088] In step 2), "prepare a polymer slurry with a concentration of 10 wt %" is changed to "prepare a polymer slurry with a concentration of 1 wt %";
[0089] The "MOF powder added in an amount of 10 wt% of the polymer mass" in step 3) is changed to "MOF powder added in an amount of 2 wt% of the polymer mass", and the rest is the same as in Example 1.
[0090] The obtained electrolyte film was used for CO2 reduction according to Experiment 1, and the Faraday efficiency of the liquid product was 61.8% and the product purity was 55%.
[0091] Comparative Example 3: The following changes were made relative to Example 1:
[0092] The step 1) of “weighing zinc nitrate hexahydrate (0.002 mol) and dissolving it in 100 mL of methanol to obtain a zinc nitrate solution with a concentration of 0.02 M” is changed to “weighing zinc nitrate hexahydrate (0.001 mol) and dissolving it in 100 mL of methanol to obtain a zinc nitrate solution with a concentration of 0.01 M”, and the rest is the same as Example 1.
[0093] The obtained electrolyte film was used for CO2 reduction according to Experiment 1, and the Faraday efficiency of the liquid product was 61.5% and the product purity was 63%.
[0094] Comparative Example 4: The following changes were made relative to Example 1:
[0095] The reaction temperature in step 2) is controlled at 70°C, which is changed to 40°C, and the rest is the same as in Example 1.
[0096] The obtained electrolyte film was used for CO2 reduction according to Experiment 1, and the Faraday efficiency of the liquid product was 48.3% and the product purity was 39%.
[0097] Experiment 2, stability test:
[0098] The membrane electrode solid electrolytes obtained from all the above cases were subjected to the following stability test: according to Experiment 1, the voltage was set to -1.0V for constant potential electrolysis experiment, and the electrolysis time when the current dropped to 80% of the initial current value was recorded, which was the stability time.
[0099] Experiment 3: Mechanical strength of membrane
[0100] The membrane electrode solid electrolyte obtained from all the above cases was subjected to the following test for the mechanical strength of the membrane: a tensile testing machine was used to test the membrane. The test parameters were set, the sample was stretched at a constant rate (5 mm / min), the stress and strain data were recorded, and the fracture strength of the sample was measured.
[0101] Tensile strength calculation formula:
[0102] Where F is the breaking load and A is the cross-sectional area (5mm 2 )
[0103] Experiment 4: The membrane electrode solid electrolytes obtained from all the above cases were subjected to the following membrane resistance test: the electrochemical workstation was set to electrochemical impedance spectroscopy (EIS) mode, the frequency range of EIS measurement was set to 1 Hz to 1 MHz, the amplitude was set to 10 mV, the impedance spectrum data was collected at room temperature, and the resistance value R of the sample was obtained by fitting the Nyquist plot or Bode plot.
[0104] The results of the above experiments 2-4 are shown in Table 1 below:
[0105] Table 1. Stability, mechanical strength and membrane resistance of different solid electrolyte membranes
[0106] Experiment 2 (Stability h) Experiment 3 (Tensile Strength MPa) Experiment 4 (Membrane resistance Ω·cm) Example 1 250 30 50 Example 2 220 28 55 Example 3 210 27 60 Example 4 230 29 53 Example 5 240 28 52 Comparative Example 1 100 15 200 Comparative Example 2 110 22 365 Comparative Example 3 120 21 268 Comparative Example 4 115 23 272
[0107] Finally, it should be noted that the above examples are only some specific embodiments of the present invention. Obviously, the present invention is not limited to the above embodiments, and there are many variations. All variations that can be directly derived or associated with the content disclosed by a person skilled in the art should be considered as the protection scope of the present invention.
Claims
1. A membrane electrode solid electrolyte, characterized in that: It is a modified MOF-based membrane electrode solid electrolyte.
2. A method for preparing a modified MOF-based membrane electrode solid electrolyte, characterized in that The following steps are involved: 1) Dissolve zinc nitrate in methanol to obtain a zinc nitrate solution with a concentration of 0.02M to 0.06M; dissolve 2-methylimidazole in methanol to obtain a 2-methylimidazole solution with a concentration of 0.04M to 0.12M; the molar ratio of zinc nitrate to 2-methylimidazole is 1:2; Add 2-methylimidazole solution to zinc nitrate solution, stir and mix, and then stand at room temperature for 12 to 24 hours to form MOF crystals; The MOF crystals are washed with ethanol; the washed MOF crystals are vacuum dried to obtain MOF powder; 2) Add tetrafluoroethylene and perfluorovinyl ether into the reactor, then add comonomer and free radical initiator to start the polymerization reaction. The polymerization temperature is 70±10℃ and the reaction time is 8±0.5h; The polymer prepolymer obtained by the polymerization reaction is subjected to heat treatment to obtain a polymer; and then the obtained polymer is dissolved in a solvent to obtain a polymer slurry, wherein the concentration of the polymer in the polymer slurry is 10 to 20 wt%; Tetrafluoroethylene:perfluoroethylene ether = 1:1 molar ratio, Tetrafluoroethylene: comonomer = 1:0.1 molar ratio; Tetrafluoroethylene: free radical initiator = 1:0.05 molar ratio; 3) adding the MOF powder obtained in step 1) to the polymer slurry obtained in step 2) and mixing them evenly to obtain a MOF modified mixture; MOF powder: polymer = 10-20wt%; 4) coating the MOF-modified mixture on a pre-cleaned substrate to form a thin film; and then drying), and then drying at 80±10° C. for 12±1 h to solidify the thin film, and finally separating the thin film from the substrate to obtain a modified MOF-based membrane electrode solid electrolyte.
3. The method for preparing the modified MOF-based membrane electrode solid electrolyte according to claim 2, characterized in that In the step 2): The comonomer is fluorosulfonic acid, and the free radical initiator is ammonium persulfate; Heat treatment is heating at 150±10℃ for 2±0.1h; The solvent was NMP.
4. The method for preparing the modified MOF-based membrane electrode solid electrolyte according to claim 3, characterized in that The uniform mixing in step 3) is stirring or ultrasonic treatment.
5. The method for preparing a modified MOF-based membrane electrode solid electrolyte according to any one of claims 2 to 4, characterized in that In the step 4), the coating is carried out by spin coating, the rotation speed of the spin coater is set to 1800-2200 rpm, and the coating time is 25-35 seconds.
6. The method for preparing the modified MOF-based membrane electrode solid electrolyte according to claim 5, characterized in that In the step 4), the substrate is a glass substrate or a silicon substrate, and acetone, isopropanol, and deionized water are used to wash the substrate in sequence to obtain a pre-cleaned substrate.
7. The method for preparing a modified MOF-based membrane electrode solid electrolyte according to any one of claims 2 to 6, characterized in that In the step 1): The concentration of the zinc nitrate solution is 0.02M to 0.04M, and the concentration of the 2-methylimidazole solution is 0.04M to 0.08M.
8. Use of the modified MOF-based membrane electrode solid electrolyte prepared by any one of claims 2 to 7, characterized in that: Used for CO2 reduction.
9. The use according to claim 8, characterized in that: The modified MOF-based membrane electrode solid electrolyte is sandwiched between the cathode (Ag) and the anode (Pt) to ensure that the modified MOF-based membrane electrode solid electrolyte is in close contact with the electrodes; CO2 is electrochemically reduced to formate ions at the cathode.
Citation Information
Patent Citations
MOFs-based solid electrolyte membrane and preparation method and application thereof
CN117691172A
Metal organic framework-based solid electrolyte as well as preparation method and application thereof
CN117895072A
MOF-ionic liquid composite solid-state polymer electrolyte, preparation method and application of MOF-ionic liquid composite solid-state polymer electrolyte in fast-charging solid-state battery
CN118367209A
Solid electrolyte
US20240396079A1